A study on corrosion behaviour of various modes of ATIG welded plain carbon steel. (2022) - Kandavel, T.K.; Panneerselvam, T.; Govind, Varun; Ravikumar, M.
Abstract: The purpose of this study is to look at the corrosion behaviour of various current modes of Autogenous Tungsten Inert Gas (ATIG) welded powder metallurgy plain carbon steel (Fe-0.5% C). The impacts of different current modes (DC, AC, Mixed, and Pulsed) on ATIG corrosion welded joints are looked at. To get the highest density, the rectangular sintered plain carbon steel strips were subjected to a cold upset. The parent and welded specimens were subjected to aqueous immersion and electrochemical corrosion tests. The corrosion test findings were compared to the microhardness, corroded surface morphology, microstructure, and SEM of the corroded area. It is observed from the test results that as the parent metal contains pores could lead to a high corrosion rate and the ATIG welded specimens exhibit less corrosion rate due to pore free region at the weldment. The DC mode of the welded specimen is observed to exhibit a lesser corrosion rate compared to the other modes of welded specimens due to higher heat generation.